2010
DOI: 10.1007/s10198-010-0277-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of presumed consent laws and institutions on deceased organ donation

Abstract: This article purports to advance the literature on the impact of presumed consent laws on deceased donation rates by examining the interactions between a presumed consent legal regime and other customs and institutions, using data on health expenditure, death rates caused by cerebro vascular diseases, motor vehicle accidents and homicides, legislation, legal systems, family consent, civil rights and liberties and donor registry systems, for 24 countries over a 14-year period. Countries in which presumed consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 18 publications
0
60
0
1
Order By: Relevance
“…20 In addition, a recent study suggested that presumed consent was only effective at increasing donation rates if accompanied by family consent programs and organ registries. 21 Moreover, numerous examples exist of countries, such as the US, which do not have a presumed-consent policy but have significantly higher donor rates than countries with presumed consent, suggesting that other processes or cultural factors may impact donation rates more strongly than policy alone. 22 Key points ■ An attenuation in the growth of deceased donor kidney transplantation has occurred in the US over the past few years ■ A critical opportunity for increasing transplantation rates is to increase the pool of available deceased donor kidneys ■ Interventions that may increase the deceased donor pool include: presumed donor consent policies, financial incentives for donors, alterations in organ allocation policies, and selective use of donors with risk for disease transmission ■ Although each of the proposed interventions has some contentious elements, they should be placed in the context of the declining prognoses of patients waiting for transplants in the setting of a growing scarcity of available organs ■ Ultimately, a systems approach that incorporates multiple interventions may be the most effective way to increase the donor pool ■ The implementation of any intervention should carefully consider multiple stakeholders and potential long-term and unintended consequences…”
Section: Presumed Consent and Opt-out Policiesmentioning
confidence: 98%
“…20 In addition, a recent study suggested that presumed consent was only effective at increasing donation rates if accompanied by family consent programs and organ registries. 21 Moreover, numerous examples exist of countries, such as the US, which do not have a presumed-consent policy but have significantly higher donor rates than countries with presumed consent, suggesting that other processes or cultural factors may impact donation rates more strongly than policy alone. 22 Key points ■ An attenuation in the growth of deceased donor kidney transplantation has occurred in the US over the past few years ■ A critical opportunity for increasing transplantation rates is to increase the pool of available deceased donor kidneys ■ Interventions that may increase the deceased donor pool include: presumed donor consent policies, financial incentives for donors, alterations in organ allocation policies, and selective use of donors with risk for disease transmission ■ Although each of the proposed interventions has some contentious elements, they should be placed in the context of the declining prognoses of patients waiting for transplants in the setting of a growing scarcity of available organs ■ Ultimately, a systems approach that incorporates multiple interventions may be the most effective way to increase the donor pool ■ The implementation of any intervention should carefully consider multiple stakeholders and potential long-term and unintended consequences…”
Section: Presumed Consent and Opt-out Policiesmentioning
confidence: 98%
“…Es por ello que la inmensa mayoría de los modelos de trasplante con buenos resultados son de consentimiento presunto, universal y restringido. España -junto con Austria-posee un modelo de consentimiento presunto, universal y absoluto 7 . Singapur aprobó la Ley de Trasplante de Ór-ganos Humanos (HOTA) en 1987, que aplica la regla de prioridad con un sistema opt-out.…”
Section: La Reforma Legislativaunclassified
“…Several studies report that presumed consent is positively correlated with higher donation rates (Abadie and Gay 2006;Johnson and Goldstein 2003;Mossialos et al 2008). Others, however, find no clearly isolable influence of presumed consent on refusal rates (Bilgel 2012;Matesanz and Dominquez-Gil 2007;Simillis 2010). In their systematic review of the existing evidence, Rithalia et al (2009: 1) conclude that "presumed consent alone is unlikely to explain the variation in organ donation rates between countries".…”
Section: Stickmentioning
confidence: 99%